ENHANCING FRACTION UNDERSTANDING THROUGH WORDWALL: A PRE-EXPERIMENTAL STUDY IN GRADE V ELEMENTARY SCHOOL - Rajaya Limho (CV Grasta Glory, 2026)
Mathematics plays an important role in developing students’ logical thinking skills; however, fraction material is often difficult for elementary students due to its abstract nature. Observations at SDN Wonokerto showed low learning outcomes and passive student participation, indicating the need for interactive learning media. This study aimed to determine the effectiveness of Wordwall media in improving fifth-grade students’ mathematics learning outcomes on fraction material. A Pre-Experimental design with a One-Group Pretest–Posttest approach was employed. The participants were 24 fifth-grade students of SDN Wonokerto. Data were collected through pre-tests, post-tests, observation, and documentation, and analyzed using descriptive statistics and a paired sample t-test. sample t-test showed a significance value of 0.000 (< 0.05), and classical learning mastery reached 79.17%. Wordwall media effectively improves fraction learning outcomes and enhances student motivation through interactive and visual learning experiences.